Accuracies based on Constitutional Law. Interview with Perfecto Andrés Ibáñez - Núñez del Prado, Fabio (2016)
In this interview, the outstanding Spanish teacher tells us from his perspective which are the main points in constitutional law. In this way, the author explain matters related to democracy, fundamental rights and the constitutional rule of law, are treated. In addition, based on a Peruvian and Spanish case the position of the teacher is explained. Finally, making brief comments, the author gives recommendations to improve the Peruvian justice system.